Short-time cycling performance in young elite cyclists: related to maximal aerobic power and not to maximal accumulated oxygen deficit - Støa, Eva Maria; Rønnestad, Bent; Helgerud, Jan; Johansen, Jan-Michael; Andersen, Ingvild Tronstad; Rogneflåten, Torkil; Sørensen, Anders; Støren, Øyvind (Frontiers in Physiology, 2025)
PurposeTo explore the relationships between performance variables and physiological variables in a short-time (2–3 min) cycling time trial (TT) on a cycle ergometer.MethodsFifteen young elite cyclists (age: 17.3 ± 0.7 years, maximal oxygen uptake (VO2max): 76.6 ± 5.2 mL⋅kg−1⋅min−1) participated in this study. Maximal aerobic power (MAP), maximal anaerobic power (MANP), time to exhaustion at 130% of maximal aerobic power (TTE), maximal accumulated oxygen deficit (MAOD) in the TT, anaerobic power reserve (APR) and lactate threshold (LT) was tested. MAP was calculated as VO2max/oxygen cost of cycling (CC), MANP was determined as mean power output (W) during a 10 s maximal cycling sprint test, and MAOD was calculated as (VO2 demand - VO2 measured) ∙ time. APR was calculated as the relative difference between MAP and MANP.ResultsThere was a strong correlation between MAP and TT time (r = −0.91, p < 0.01) with a standard error of estimate (SEE) of 4.4%, and a moderate association between MANP and TT time (r = −0.47, p = 0.04). Neither MAOD, TTE, LT nor APR correlated with TT.ConclusionMAP was highly correlated with TT with a SEE of 4.4%. Since neither TTE nor MAOD correlated with TT, this indicates that these two variables do not play a significant role in differentiating short-time endurance cycling performance. We suggest training for improving MAP and, or MANP to improve short-time endurance cycling performance.